Corpo Docente Atual - Espaço Aberto, Revista (Espaço Aberto, 2022)
Profa. Ana Luiza Coelho Netto Profa. Ana Maria de Souza Mello Bicalho Prof. André de Souza Avelar Prof. Antônio José Teixeira Guerra Profa Carla Bernadete Madureira Prof. Claudio Antônio Gonçalves Egler Profa. Elizabeth Maria Feitosa da Rocha de Souza Profa. Eve Anne Buhler Profa. Flavia Moraes Lins de Barros Prof. Frédéric Monié Profa. Gisela Pires do Rio Profa. Gislene Aparecida dos Santos Profa. Iná Elias de Castro Profa. Júlia Adão Bernardes Profa. Lia Osório Machado Prof. Manoel do Couto Fernandes Prof. Marcelo Lopes Prof. Marcos Paulo Ferreira de Góis Profa. Maria Naíse de Oliveira Peixoto Profa. Mônica dos Santos Marçal Prof. Nelson Ferreira Fernandes Profa. Núbia Beray Armond Prof. Paulo César da Costa Gomes Prof. Paulo Márcio Leal Menezes Prof. Paulo Pereira Gusmão Prof. Rafael da Silva de Barros Prof. Rafael Winter Ribeiro Profa. Rebeca Steiman Prof. Ricardo Gonçalves César Prof. Roberto Lobato Correa Prof. Scott William Hoefle Profa. Telma Mendes da Silva Prof. William Ribeiro da Silva